Tibial internal and external rotation taping for improving pain in patients with patellofemoral pain syndrome. Issue 8 (August 2022) - Deng, Fawei; Adams, Roger; Pranata, Adrian; Cui, Fang; Han, Jia
Abstract: Objectives: The aim of this study was to assess the effects of two rigid taping methods, tibial internal rotation taping and external rotation taping, on knee pain during three clinical function tests in individuals with patellofemoral pain syndrome. Design: Repeated measures study. Methods: Fifteen participants (male, height 174.9 ± 5.8 cm, weight 68.3 ± 10.2 kg) with unilateral patellofemoral pain syndrome were treated by applying internal rotation taping and external rotation taping, in randomized order. While taped, participants were asked to perform three clinical tests in random order: single-leg squat, double-leg squat, and quadriceps maximum isometric contraction. Pain was scored using a Visual Analog Scale. Results: Compared with no taping, both internal rotation taping and external rotation taping significantly improved pain during each of the three clinical tests (F = 224.10, p  < 0.001, partial η² = 0.94). Furthermore, there was a tape direction effect, where external rotation taping was more effective than internal rotation taping (F = 4.90, p  = 0.044, partial η² = 0.26). For each test, the amount of pain improvement after taping was positively correlated with initial pain level (0.539 ≤  rho  ≤ 0.921, all p  < 0.05). Conclusions: Both internal rotation taping and external rotation taping were effective in improving pain in individuals with patellofemoral pain syndrome, and external rotation taping was more effective than internal rotation taping. The significant correlations observed between initial pain levels and pain improvement after taping suggest that those with greater patellofemoral pain achieve greater relief from tibial rotation taping.